Analisis Waste Pembuatan Tahu Untuk Perbaikan Kualitas Dengan Menetapkan Waktu Standar - Ana Yulita Da Silva; Suntoro Suntoro; Rizqi Permana Sari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Mahrup Cibogo Tofu Factory is a small-scale business that has been producing white and yellow tofu since 1979, founded by Mr. Mahrup. Currently, the factory is facing quality issues such as defective products including misshapen tofu, tofu with holes on the surface, inconsistent sizes, and contamination. These defects are mainly caused by time inefficiencies in the production process due to the absence of established standard time and lack of a Standard Operating Procedure (SOP), leading workers to rely on their personal experience without consistency. This research aims to assist the factory by analyzing the root causes of product defects and determining standard times for each production stage. Tools like histograms, Pareto diagrams, P-Charts, and fishbone diagrams are used to identify the defects, while work time measurements are used to calculate standard time. The results show that the most common defect is shape damage at 31.6%. The total standard time for the complete tofu production process is 217.68 minutes (3 hours and 38 minutes). The proposed improvements include implementing the suggested SOP to minimize waste, control product quality, and provide clear work guidelines for employees